Acinetobacter infections: a retrospective study to determine inhospital mortality rate and clinical factors associated with mortality. Issue 2 (June 2019) - Patel, R.V.; Shah, J.S.; Revathi, G.; Siika, W.; Shah, R.
Summary: A retrospective case series of acinetobacter infections at a tertiary hospital in Nairobi was conducted to determine the mortality rate and factors associated with mortality. Over an eight-year period, 80 clinically significant infections were identified. The majority of infections were ventilator-associated pneumonia (40%) and bloodstream infections (30%). Eighty-six percent of the isolates were multi-drug resistant. The mortality rate in the study cohort was 45%. Twelve patients grew Acinetobacter spp. within 48 h of hospitalization, and three of these patients had no prior healthcare contact. The mean Sequential Organ Failure Assessment score was associated with mortality from acinetobacter infections.